Synergism of Cefazolin-Gentamicin Against Enterococci - Bourque, Michael (1976)
A miniaturized technique for detecting antibiotic synergy by using microliter volumes was perfected. With this microtiter serial dilution method, the effect of the previously untried combination of cefazolin and gentamicin on 10 strains of enterococci was evaluated. At clinically achievable concentrations, the combination of cefazolin and gentamicin was found to be synergistic against all 10 strains when the data were plotted in the form of an isobologram. These results were compared with the conventional method of detecting synergy in vitro, namely, the determination of the rate of killing of the microorganisms with the antibiotics, singly and in combination. Similar results were also observed. These findings indicate that the microtiter serial dilution technique is a useful method for the routine determination of drug synergy. Moreover, in a patient with penicillin hypersensitivity and enterococcal infection, the combination of cefazolin and gentamicin should be considered for possible therapy.